Study of the effect of culture conditions on metabolite production by endophytic strain SK9 (OS MAC) / Faradia Mohmad - Mohmad, Faradia (2008)
The major objective of this project is to determine the effect of culture condition on metabolite production by endophytic fungal strains SK9. There are two culture condition involve in this study which are potato dextrose agar and potato dextrose broth. First step was growing the endophytic fungal strain on sol.d agar and static broth media. The resulting extracts were taken as subjected for antimicrobial activity testing against selected bacteria and fungi by disc diffusion method. The HPLC analysis also been done in order to detect secondary metabolites resulting from the acculturation of the fungal strain SK9 in different media. Throughout the whole stage, fungi were observed macroscopically and microscopically. The observations were recorded and shall be included into the database developed by Faculty of Pharmacy, UiTM.